Linguagem, trabalho e educação: estudo exploratório de livros didáticos para E.J.A. - Clarice Lage Gualberto (2012)
The current work is a linguistic discourse analysis of some Didactic Materials (DMs) directed for the Adult Education (YAE). It searches for the DMs contributions to the development of these students' critical thinking and how they present the work them. Therefore, based on authors such as Bakhtin / Voloshinov (2004), Fiorin (2007), Ana Lúcia de Faria (1995) and Ducrot (1987), two excerpts which have as the main theme the work concept, from the following books: Adult Education: New Life project. (OLIVEIRA (coord.), 2007) and To live, to learn: adult education (VÓVIO; MANSUTTI (coord.), 2004), designed to the primary and the elementary school, respectively. We investigate feasible meanings and discourses produced by the selected DMs. Our research has revealed that both textbooks have as their main educational goals the reflexive skills development. And in order to achieve it, linguistic skills are emphasized; inferences of the implicit are the main linguistic skill throughout the textbooks. We believe this research may contribute linguistic and educationally to the several people involved in the YAE, mainly, besides other reasons, because the work theme is much more related to the YAE students profile than to the children, students from the regular school.